Synthesis, Structure and Dielectric Properties of Magnesium-substituted Lithium Ferrite - L.S. Kaykan; J.S. Kaykan; I.P. Yaremiy; O.M. Ugorchuk; B.Y. Deputat; M.O. Nykoliuk (Журнал нано- та електронної фізики)
By using method of sol-gel autocombustion was obtained single-phase ferrite with space group and crystallite size of 35 nm. Based on temperature impedance research was revealed a strong dispersion of the real part of the dielectric constant at low frequencies. It caused by the dipole-orientation polarization and polarization between boundaries. The conductivity of the synthesized system has semiconductor type. For it two mechanisms of conductivity are inherent activation type in high-temperature area and hopping type in room temperature area.